Peta Perkembangan Penelitian Pemanfaatan Repositori Institusi Menuju Open Access: Studi Bibliometrik dengan VOSViewer - Tupan Tupan (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2016)
The study is aimed to know the development mapping in using open-access institutional repositories. It has been researched in August 2016 by using scopus databases with keywords: open access and institutional repository. The results findings are descriptively analysed according to publication years, institution and country names, journal names, document types, and research topics. To gather the research development mapping, the data were exported  by using CSV format (Comma Separated Values). These data then being processed and analysed using VOSViewer application program. The study found that the research development mapping have been occurred since 1986. From 2002-2016, the mapping have been significantly increased. The journals that mostly published its trends were OCLC System and Services, Lecture Notes in Computer Science, Grey Journal, Information Services and Use, Liber Quarterly, Library Review, and Serial Librarian. Meanwhile, the most type of documents were articels, conference paper, review, and book chapters. For the topic of research, it is found that open access, institutional repositories, societies and institutions, information services, digital libraries, metadata, and electronic publishing were dominant. The visual network has shown that the relationship among topics can be seen from descriptor lines in each field. The more relation descriptor lines the closest realtionship among documents.